1997
DOI: 10.1046/j.1365-2141.1997.232666.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of IL‐6 receptor expression in fresh childhood Burkitt's lymphoma cells and induction of IL‐6 receptors by Epstein‐Barr virus in vitro

Abstract: Summary. Interleukin-6 (IL-6) is a cytokine which is necessary for the differentiation of activated B cells and growth of early haemopoietic progenitors. It is used for exvivo expansion of myeloid progenitors in the setting of highdose chemotherapy with autologous bone marrow transplantation (BMT). Expression of the IL-6 receptor (IL-6R) was examined in six fresh Burkitt's lymphoma (BL) cell preparations and 12 BL cell lines by reverse transcriptase polymerase chain reaction (RT-PCR) and flow cytometry (FCM). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Tupitsyn et al [7] described that the majority of B cell tumours expressed either IL-6R or gp130. Tomeczkowski et al [8] and Klein et al [9] found IL-6 receptors only in B cell lymphoma cell lines infected by EBV. The membrane protein gp130 was expressed in all investigated MM cell lines and all B cell lymphoma cell lines.…”
Section: Discussionmentioning
confidence: 98%
“…Tupitsyn et al [7] described that the majority of B cell tumours expressed either IL-6R or gp130. Tomeczkowski et al [8] and Klein et al [9] found IL-6 receptors only in B cell lymphoma cell lines infected by EBV. The membrane protein gp130 was expressed in all investigated MM cell lines and all B cell lymphoma cell lines.…”
Section: Discussionmentioning
confidence: 98%
“…Genes repressed by MPA in normal lymphocytes included interleukin 6 (IL-6) and IL-1. 41 The production of IL-6 acts as a proproliferative autocrine signal for in vitro EBV-transformed B cells, although whether this mechanism extends to primary BL cells remains controversial. [41][42][43][44] There is unconvincing evidence that IL-6 serves to support the survival of childhood BL, but there are a growing number of reports that indicate that this mechanism is a key feature of AIDS-related BL and other HIV-associated lymphoproliferative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…41 The production of IL-6 acts as a proproliferative autocrine signal for in vitro EBV-transformed B cells, although whether this mechanism extends to primary BL cells remains controversial. [41][42][43][44] There is unconvincing evidence that IL-6 serves to support the survival of childhood BL, but there are a growing number of reports that indicate that this mechanism is a key feature of AIDS-related BL and other HIV-associated lymphoproliferative diseases. 42,43,45 In contrast, IL-1b is expressed by both EBV-transformed lymphoblastoid cell lines and BL cells and was shown to be upregulated by several EBV latent proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We detected gene expression of MDC, IL6R as well as SIRP␣, adhesion molecule LFA1, anti-apoptotic A-20, signal regulatory SLP76, and BCAR3, DNA binding proteins EGR2 and DEC1 in BCR cross-linked Burkitt's Lymphoma BL2 cell. It is known that MDC in unstimulated B cell lineage (8) and IL6R in BL2 cell line are not expressed (9,10). LFA1 molecule is significantly up-regulated upon B cell stimulation with anti-IgM and IL4 (11).…”
Section: Resultsmentioning
confidence: 98%